Model Predictive Control of Wind-Photovoltaic Hybrid System Connected to Grid - Houda Abidi; Abdelkader Mami (IAES International Journal of Robotics and Automation (IJRA), 2017)
This work focuses on Model based Predictive Control (MPC) for photovoltaic-wind hybrid energy system connected to electrical grid. Several benefits  are offered by this method  such as robustness against a  parameter variations, minimum output current distortion and excellent reference tracking. In order to minimize the cost function or the error between the  predicted values and their references, MPC-based algorithm permit to select and apply the  optimal voltage vector. Simulation results under Psim environment show a fast dynamic behavior of hybrid system with minimal errors, accuracy and usefulness of the considered control approach.